ANTIMICROBIAL ACTIVITY AND MECHANICAL PROPERTIES OF EDIBLE FILM ENRICHED WITH FINGERED CITRON WATER EXTRACT AND PROBIOTIC - HILAL TASBASI; MELTEM ASAN-OZUSAGLAM (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Food consumption is vital, so edible and biodegradable materials are being developed against environmental factors. The aim of the study was to develop edible film containing fingered citron leaf extract and determine its biological activities and mechanical properties. In the study, the antimicrobial effect of fingered citron water (FCW) extract against pathogens was determined by disc diffusion, micro and macro dilution tests. Additionally, the antimicrobial activity of edible films containing the extract and Limosilactobacillus fermentum MA-7 was determined by well diffusion assay. The highest and lowest inhibition diameter of extract against pathogens was detected for Escherichia coli O157:H7 (11.61 mm) and Vibrio anguillarum A4 (9.09 mm). Minimal inhibition and bactericidal concentration (MIC and MBC) values ranged between 5 - 40 µg·µL-1. Also, it was determined that FCW extract prepared at 50 and 100 mg·mL-1 concentration had an inhibitory effect against E. coli O157:H7 at 0, 24 and 48th hours by viable cell count. Then, the antimicrobial activity of the prepared films was evaluated and the highest and lowest inhibition zone diameters against E. coli O157:H7 (12.85 mm) and Streptococcus agalactiae Pas. Ins. (4.02 mm) were determined. It was determined that the edible film prepared with FCW extract and probiotics has the potential to protect against food spoilage.